Factors Affecting School Performance in the Adolescents of USA- Youth Risk Behavior Surveillance System. (1st June 2022) - Chahal, M.; Telsem, M.; Das, B.; Patel, S.; Gadiwala, S.; Stuart, R.; Mistry, A.; Satnarine, T.; Singla, P.; Bakarr, A.; Sharma, P.; Hsieh, Y.-C.; et al.
Abstract : Introduction: Poor academic performance has been linked to factors such as sleep, health, illicit drug use, physical fighting, social media use, cyber bullying, physical activity, homelessness, times spent in video games and television. It is difficult to get a sense of the interplay between and relative importance of different behaviours/factors on academic performance as only limited research has been aimed at quantifying these factors. Objectives: To evaluate association of school performance and variables in five categories of the YRBSS: physical fighting, diet/lifestyle, electronic device usage, concurrent substance use, and violence/self-harm. Methods: The CDC Youth Risk Behavior Surveillance System (YRBSS) data from 1991-2019 was used in study. Respondents were grouped by good and poor school performance and variables related to nutrition/lifestyle, electronic device use, concurrent substance use, mood/violence/self-harm were analyzed using chi-square test. Results: A total of 41, 235 student respondents.Nutrition/Lifestyle, electronic device use, concurrent substance use, mood/violence/self-harm are found to be significantly correlated with school performance. Conclusions: In national data, we found school performance is affected by nutrition, lifestyle, substance use, mood and exposure to surrounding violence, and self-harm. Further studies should be planned to evaluate benefits from the risk stratification to reduce this burden amongst US adolescents. Disclosure: No significant relationships.